Field analyzers for lead quantification in drinking water samples. Issue 20 (27th August 2021) - Doré, Evelyne; Lytle, Darren A.; Wasserstrom, Lauren; Swertfeger, Jeff; Triantafyllidou, Simoni
Abstract: Field analyzers for the measurement of lead in drinking water samples are gaining interest from states, water utilities and building managers as rapid, inexpensive and simple tools to quantify lead concentrations. This literature review compares data quality by field analyzers to established laboratory methods and provides practical information (e.g. costs, ease-of-use) on commercial lead analyzers that are based on: (1) Electrochemistry, (2) Colorimetry and (3) Fluorescence. Between and within these three general field analyzer categories, manufacturers specify a variety of protocols to prepare the samples, which differ from the standard acidification in laboratory methods. Review of the literature raised concerns that without adequate sample preparation, field analyzers may not always fully quantify the total lead concentration, including particulate lead, thereby resulting in underestimations. Nonetheless, field analyzers have been used to quickly obtain experimental results in the laboratory, or in the field when access to laboratory equipment was limited, expensive or otherwise impractical. Field analyzers were also successfully used to detect lead from service lines, by a water utility where lead was mostly in the dissolved form. Overall, intrinsic strengths and weaknesses of field analyzers are discussed, to better balance practical convenience and adequate data quality depending on the objective. Abstract : UF0001